Models of accessing crisis management of enterprises in terms of COVID-19 - Kolupaieva, I. V.; Afolabi Ibrahim, F. О. (ХНУРЕ, 2021)
A crisis in an enterprise environment corresponds to any negative unconventional, unexpected situation having the notable potential to cause an unstable and dangerous situation affecting an enterprise stakeholder as well as the enterprise at large
Keywords: стратегії економічного розвитку; бізнес-освіта